Islam, constitutional law, and human rights : sexual minorities and freethinkers in Egypt and Tunisia - Virgili, Tommaso (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book explores how Islam, its laws and principles, affects individual liberties. It focuses on the constitutions of Tunisia and Egypt, two countries which have experienced at least partial democracy following the Arab Spring. The work examines a number of sensitive topics from an Islamic perspective, and concludes with two specific case studies in the concerned countries"--
Introduction -- Constitutionalism and Islam -- The Islamic conception of individual liberties -- What "sharia" in a constitution concretely means : the case of Egypt -- Islamic law in post-Arab spring Egyptian constitutions -- Compromises and ambiguities in the 2014 Tunisian constitution -- Introduction to the case studies -- (Il)legal persecution of freethinkers -- (Il)legal persecution of sexual minorities -- Constitutional and international freedoms -- Conclusions -- Constitutions and individual freedom: the unbreakable bond.
Keywords: Constitutional law (Islamic law); Civil rights (Islamic law); Constitutional law -- Egypt; Constitutional law -- Tunisia; Civil rights -- Egypt; Civil rights -- Tunisia; LAW / General; LAW / Civil Rights; LAW / Comparative